2020
DOI: 10.2217/rme-2019-0143
|View full text |Cite|
|
Sign up to set email alerts
|

One Health in Regenerative Medicine: Report on the Second Havemeyer Symposium on Regenerative Medicine in Horses

Abstract: Regenerative medicine is commonly used in human and equine athletes. Potential therapies include culture expanded stem cells, stromal vascular fraction of adipose tissue, platelet-rich plasma, bone marrow concentrate, or autologous conditioned serum. The purpose of this manuscript is to disseminate findings from a workshop on the development of translational regenerative medicine in the equine field. Five themes emerged: stem cell characterization and tenogenic differentiation; interactions between mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…This increased use may be attributed to increased commercial availability and advertisement of biologic products coupled with extensive literature surrounding the use of biologic therapies for musculoskeletal disease. 20 Platelet-rich plasma was the most widely used biologic therapy by large animal diplomates. Despite the differences in survey populations, our study and Velloso et al (2020) indicated that PRP was the most widely used biologic therapy for musculoskeletal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased use may be attributed to increased commercial availability and advertisement of biologic products coupled with extensive literature surrounding the use of biologic therapies for musculoskeletal disease. 20 Platelet-rich plasma was the most widely used biologic therapy by large animal diplomates. Despite the differences in survey populations, our study and Velloso et al (2020) indicated that PRP was the most widely used biologic therapy for musculoskeletal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested a similar level of use amongst large animal specialists, irrespective of their duration in practice or practice type. This increased use may be attributed to increased commercial availability and advertisement of biologic products coupled with extensive literature surrounding the use of biologic therapies for musculoskeletal disease 20 …”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem/stromal cells (MSCs) are adult multipotent stem cells that have attracted significant interest for regenerative medicine due to their distinct biological properties ( 1 , 2 ). Since the underlying causes of certain diseases are similar in both people and animals, the findings obtained from MSC research can be valuable for both human and veterinary patients, promoting the concept of “One Health, One Medicine” ( 3 , 4 ). Horses are of particular importance in translational medicine, as they suffer from various pathologies analogous to human with inflammatory and immune components, in which the ability of MSCs to modulate the immune system through their paracrine activity has broadened the scope of potential applications ( 5 ).…”
Section: Introductionmentioning
confidence: 99%